PENGARUH SISTEM PENGAMANAN OBJEK VITAL, FILE DAN CYBER TERHADAP MANAJEMEN SEKURITI PADA PT PLN (PERSERO) TBK - Edy Soesanto; Dwi Putri Aprillia; Nawang Dwi Anjani; Halimatusa’diah Halimatusa’diah (Cross-border, 2023)
PLN is a State-Owned Enterprise that handles government problems related to electricity and supplies electricity in very large quantities to the population. At PT. PLN is a subsidiary engaged in Power Plants, in this sector a vital object security system is urgently needed which is directly monitored by The Regional Police Vital Object Security Unit where the work system at PT. PLN is carried out by members of security, namely security guards. Therefore, an Android-based application is needed for monitoring the security of vital object areas which is a container for reporting vital objects in realtime that is integrated in one Information Technology system under the auspices of the PAM OBVIT POLDA JAMBI with an emphasis on prevention, speed of action of officers and ease in securing the location of vital objects in the environment. PLN DALKIT JAMBI Province. Data confidentiality ensures that cyber users have their privacy protected, be it privacy on personal computers, handheld devices or protected by privacy data when carrying out various internet browsing activities. Cyber-security is a collection of tools, policies, security concepts, security safeguards, guidelines, risk management approaches, measures, training, best practices, assurance and technology that can be used to protect the cyber environment and the organizations and assets of users.